A multivariate discrete failure time model for the analysis of infant motor development. (28th November 2018) - Neelon, Brian; Shoaibi, Azza; Benjamin‐Neelon, Sara E.
Abstract : We develop a multivariate discrete failure time model for the analysis of infant motor development. We use the model to jointly evaluate the time (in months) to achievement of three well‐established motor milestones: sitting up, crawling, and walking. The model includes a subject‐specific latent factor that reflects underlying heterogeneity in the population and accounts for within‐subject dependence across the milestones. The factor loadings and covariate effects are allowed to vary flexibly across milestones, and the milestones are permitted to have unique at‐risk intervals corresponding to different developmental windows. We adopt a Bayesian inferential approach and develop a convenient data‐augmented Gibbs sampler for posterior computation. We conduct simulation studies to illustrate key features of the model and use the model to analyze data from the Nurture study, a birth cohort examining infant health and development during the first year of life.